Big Five of Personality and Cognitive Style Big Five Factors of Personality and Reflection – Impulsivity Cognitive Style: A Cross- Cultural Study - Khalil, Elham A. (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2019)
Objective: This study examines the differences between individual culture (American sample) and collective cultures (Egyptian and Saudi Arabian samples) in Reflection- impulsivity (RI) categories and Big Five of personality traits. The relative contribution of Big Five of personality traits and culture are predicted with RI categories.Method: Computerized MFFT and NEO PI R administrated on 53 male and female Egyptian, 51 female Saudi, and 35 male and females Americans students.Results: Using (Z) ratio, results showed no differences among three cultures in MFFT categories except Saudi who were more slow- inaccurate than Egyptian students. Using ANOVA to know significant differences among three cultures on NEO- PI R facets and dimensions. Egyptian were more (O1), (N2), and (E5) than were the Saudi students; Saudi students were more (A3) (A4), (A6), (C4), and agreeableness than were the Egyptian, and more (C2) than American; American who were more (O1), and (E6) than were the Egyptian students, and more (O1), (E5) and (E6) than were the Saudi students.Conclusions: The culture variable was not predicted with MFFT’ categories, except the Egyptian students who were more inefficient than were the American students as a reference group, and with multinomial regression analysis, only extraversion dimension expected to impulsivity.